Studies on Length of Apron and End Sill Height in Straight Drop Spillway Stilling Basin - hakim, A A; Satyanarayana, T (Journal of Soil and Water Conservation, 2022)
Most failures in the proper functionting of the canal drops, control gully erosion and grade structures are due to bed scour and undermining of the apron together with erosion at the toe of the embankments on either side of the structure. Evidently, these failures are caused by inadequate dissipa- tion of energy of the falling body of water. The complexity of this phenomenon involving innumerable known and perhaps some unknown variables does not lend itself to the application of strict mathematical analysis in order to determine the dimensions of a most economical, hydraulically sound and efficient structure which would not fail in use. Such a problem can more successfully be tackled by means of model studies for a set of given hydrological, topographical and soil conditions.